KAJIAN POLA KONTROL PRIVASI PENGHUNI TERHADAP PENERAPAN KONSEP SOHO (SMALL OFFICE HOME OFFICE) PADA RUMAH TINGGAL DI KOTA BANDUNG - TODDY HENDRAWAN YUPARDHI; DEDDY WAHJUDI; BAGUS HANDOKO (Serat Rupa: Journal of Design, 2016)
The effect of various urban problems and the increasing of advanced information technology, leading the concept of SOHO (Small Office Home Office) as an alternative solution in operating small- to medium-scale home-based business are set to have significant application in recent years in Indonesia. Yet the context of residential home as a private space for activity of a family live is resulting in chances of privacy conflicts when it is matched to concept of SOHO application inclining to have social and open-ended characteristics for the public. Therefore, the privacy control is necessary for maintaining dwellerâ€™s privacy and homeostatic condition in residential home.The aim of this research was to understand how was the pattern of privacy control by means of visual, audio, and olfactory interaction that take place in 10 residential home units chosen for object of study. This research is a qualitative study which delivered descriptively through interpretative analysis using theory of Behavior Setting approach, and such supporting theories as dwelling theory, theory of adaptation and adjustment, theory of privacy, territorial, and personal space. The results of the research shown that the privacy control pattern is more intomanaging visual interaction related to privacy by means of privacy artifact control, differentiation of floor level or using verbal language. Overall results of analysis of privacy control variable are then proposed as tendency of dweller privacy control design to apply concept of SOHO to residential home.Â Keywords: control; home, office; privacy; SOHO